YTHDF2 promotes the liver cancer stem cell phenotype and cancer metastasis by regulating OCT4 expression via m6A RNA methylation - Zhang, Chuanzhao; Huang, Shanzhou; Zhuang, Hongkai; Ruan, Shiye; Zhou, Zixuan; Huang, Kaijun; Ji, Fei; Ma, Zuyi; Hou, Baohua; He, Xiaoshun (Oncogene, 2020)
N -methyladenosine (m6A) RNA methylation contributes to the cancer stem cell (CSC) phenotype through regulating gene expression. YTHDF2, an m6A reader, was shown to be associated with hepatocellular carcinoma (HCC) patient prognosis. However, the effect of YTHDF2 on liver CSC and cancer metastasis and the molecular mechanism of this effect have not been documented. Here, we show that YTHDF2 expression is negatively correlated with HCC patient survival in both data from the Cancer Genome Atlas (TCGA) database and clinical data from our center. By detecting CD133 cells and carrying out sphere culture assays, we found that knockdown of YTHDF2 led to impaired stemness in Hep3B and Huh7 cells. In contrast, overexpression of YTHDF2 increased the CSC phenotype. Mechanistically, the knockdown and overexpression of YTHDF2 in liver cancer cells resulted in decreased and increased m6A levels in the 5'-untranslated region (UTR) of OCT4 mRNA, respectively, leading to decreased and increased OCT4 protein expression, respectively. A luciferase activity assay showed that mutation of the corresponding m6A methylation sequence in the 5'-UTR of OCT4 mRNA caused significantly decreased gene expression, suggesting a role for YTHDF2-dependent m6A methylation in protein translation. Polysome profiling results also indicated the knockdown and overexpression of YTHDF2 could decrease and increase OCT4 translation, respectively. In particular, overexpression of OCT4 rescued the impaired stemness caused by YTHDF2 depletion, which confirmed the effect of YTHDF2 on CSC phenotype is dependent on OCT4. In vivo, the loss of YTHDF2 reduced tumor burden and inhibited lung metastasis following orthotopic transplantation in nude mice. Last, we demonstrated that YTHDF2 expression is positively correlated with OCT4 expression and m6A levels in the 5'-UTR of OCT4 mRNA in clinical HCC specimens. In conclusion, YTHDF2 promotes the CSC liver phenotype and cancer metastasis by modulating the m6A methylation of OCT4 mRNA.